A Conversation with K. N. Afanasiev - Bagina, Elena (project baikal, 2019)
In the summer of 1986, Kirill Nikolaevich Afanasiev told Oleg Yavein and Elena Bagina about the architects, sculptors and artists whom he used to know and work with. K. N. Afanasiev’s memories of Zholtovsky, Shchusev, Alabyan, Burov, Sinyavsky, Mordvinov, Shadr, Merkurov and others cannot be found in any book. These are the living testimonies of the man, for whom A. A. Vestin was a teacher, M. Ya. Ginsburg was a fellow at the Association of Contemporary Architects, and I. V. Zholtovsky was a coworker.